Assessing the Role and Viability of Nuclear Power in Ukraine’s Post-War Energy Strategy - Osadcha, Natalia; Zaverbnyj, Andrij (European Journal of Sustainable Development, 2024)
Ukraine’s nuclear power industry is partially under russian occupation, which poses a significant energy threat. This applies to both Ukraine and European countries. Nuclear power plants in Ukraine operate on imported uranium. The article analyses trends in the development of nuclear energy in the world and in Ukraine. The energy system of Ukraine depends on imported uranium. The article presents an assessment of the exhaustibility of uranium resource. Steps to improve the safety of nuclear energy are presented and the necessity of transition to green energy is substantiated. The problems of atomic energy of Ukraine in conditions of sustainable development are analysed. Keywords: energy, uranium, resource exhaustibility, energy strategy, nuclear power plants